Terms and Conditions for Objection, Appeal And Reconsideration in the Tax Court - Alya Shafadilla; Rini Dyah Puspo Sari; Sausan Qorina; Galuh Tresna Murti (Jurnal Riset Perpajakan: Amnesty, 2023)
This study aims to explain the terms and conditions of objection, appeal and review. The legal remedy that can be taken by taxpayers in the event of a tax dispute is by filing an objection. if you feel dissatisfied with the results of the objection, you can proceed by filing an appeal to the tax court. In principle, the tax court's decision is final and has permanent legal force, nor can a lawsuit be filed in a general court, state administrative court, or other judicial body. However, if the disputing parties are dissatisfied with the tax court decision, it is still possible to take the last resort in the form of extraordinary legal remedies, namely by submitting a judicial review of the tax court decision to the Supreme Court.